Factors influencing consumers’ purchase intention on organic foods via a Theory of Planned Behaviour approach - Cheng, Su-Juan; Jia, Hao-Xiang; Philip Pong Weng , Wong; Wang, Lei (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2023)
Even though Asian countries are expected to become a dominant market for organic foods in the coming years, there are few studies which focused on young Asian consumers’ organic food purchase behaviour. This study aims to investigate how attitude, subjective norm, perceived behavioural control, and health concerns influence consumers’ intention to purchase and consume organic foods. A purposive sampling method was adopted for this study and a total of 289 usable questionnaires were collected for empirical testing of the postulated hypotheses using SPSS and structural equation modelling (SEM). The results showed that attitude, subjective norm, perceived behavioural control and health concern positively influenced intention. In addition, subjective norm positively influenced attitude while attitude played a partial mediation effect on the relationship between subjective norm and intention. Lastly, the theoretical and practical implications as well as the limitations of the study are discussed.